Tanzania : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency for Tanzania. Tanzania has implemented a number of reforms in recent years to enhance fiscal transparency. The most notable reforms in fiscal management are: implementation of a comprehensive Integrated Financial Management System; institution of a public expenditure review process on a continuous basis in the context of a medium-term expenditure framework; and enactment of a new legal framework for fiscal management and procurement. Many new initiatives are in the process of being implemented to further enhance fiscal transparency and good governance.